The Role of Work-Life Harmony on Job Satisfaction of Generation Z Employees in Banyumas: The Role of Work-Life Harmony on Job Satisfaction of Generation Z Employees in Banyumas - ADI SETIAWAN RISQI RISQI; Shalsabilla Novarizka; Asma Sa'adati Rizqillah (Universitas Indo Global Mandiri Palembang, 2025)
Objective: This study aims to analyze the influence of work-life harmony on job satisfaction among Generation Z employees in Banyumas Regency. Generation Z, known as digital natives, exhibits unique characteristics in the workplace, such as a preference for flexible schedules, work-life balance, and work environments that support mental well-being. Design/Methods/Approach: Using a quantitative approach and a cross-sectional design, the study involved 200 respondents selected through purposive sampling. Data were collected using the Work-Life Harmony Questionnaire by Katrina Murphy Coaching and a job stress scale developed based on job satisfaction dimensions proposed by Luthans (2006). Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings: The results indicate that work-life harmony has a positive and significant effect on job satisfaction (β = 0.609; T = 12.887; p < 0.001). These findings are supported by various theoretical frameworks, including the Conservation of Resources Theory, Self-Determination Theory, and Person-Environment Fit Theory, which emphasize the importance of role harmony in maintaining psychological well-being. The study concludes that work-life harmony is a strategic factor in enhancing job satisfaction among Generation Z employees, especially in regions with collectivist cultural values such as Banyumas. Originality/Value: While previous studies have predominantly focused on work-life balance, limited attention has been given to the concept of work-life harmony particularly in the context of Generation Z in Indonesia. This study offers a novel contribution by adopting the work-life harmony framework, which better reflects the integrative and value-driven preferences of digital natives. The use of PLS-SEM further strengthens its methodological value, providing relevant insights for the development of flexible and adaptive work policies. Practical/Policy implication: The results offer valuable implications for organizations in designing flexible, adaptive, and employee-centered work policies that support the integration of professional and personal life roles.